Penatalaksanaan Fisioterapi dengan Modalitas Transcutaneous Electrical Stimulation (TENS) dan Terapi Latihan Terhadap penurunan Nyeri dan dan Peningkatan Aktivitas Fungsional Pada Pasien Ostheoarthritis Genu - hardini, kurniani fatma (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The higher life expectancy will increase degenerative diseases and disabilities for elderly. Osteoarthritis genu is a degenerative disease due to abrasion of joint cartilage and the formation of new bone on the joint surface, causing difficulty in carrying out activities. Osteoarthritis genu causes disturbances including pain and decreased daily functional activities. The purpose of this study was to determine the management of physiotherapy with transcutaneous electrical stimulation (TENS) and exercise therapy to reduce pain and increase functional activity in patients with osteoarthritis genu. This writing method uses a case study of genu osteoarthritis sufferers at Gambiran Hospital, Kediri City, the frequency of which is 4 times therapy using TENS with a frequency of 100 Hz, 15 minutes, and Exercise Therapy using isotonic exercise and isometric exercise 5 times repetition with 5 counts. Pain was measured using the VAS and functional activity was measured using the womac index. The results showed that TENS and exercise therapy can reduce pain and increase functional activity in patients with osteoarthritis genu.